Commensality practices among university students - Fontela Baptista, Eduarda; Carneiro Almeida, Lana; Fagundes, Glaura Paulo; de Vargas Zanini, Roberta (O Mundo da Saúde, 2022)
The Food Guide for the Brazilian Population addresses guidelines for an adequate and healthy diet, including recommendations on the act of eating and commensality. When entering university life, students tend to change their routine, which contributes to having quick, irregularly scheduled, and nutritionally inadequate meals. The aim of the present study was to investigate commensality practices and associated factors in newcomers to a public university in Rio Grande do Sul. This is a cross-sectional study carried out in 2019. The outcome consisted of the Guide's direction on eating in with others and participation in activities involving food. The exposure variables investigated were sex, age, housing composition, paid work, economic class, and university study period. Of the 207 participants, 83.9% and 62.4% reported that they usually have lunch and dinner together, respectively. Most students participate “sometimes” in planning (49.8%) and preparing meals (50.5%), and “always” participate in buying food (51.2%) and cleaning utensils and environment (62.8%). In addition, most students aged 30 years or older reported that they usually have breakfast together (p=0.010), while students who live with family members are the ones who most eat the three meals together (p<0.05). There was a higher frequency of women participating in planning (p=0.012) and meal preparation (p=0.002). It is concluded that, in general, students practice commensality, with a higher occurrence among those who live with family members.